Analisis Puisi “pada suatu Hari Nanti” Karya Sapardi Djoko Damono: Kajian terhadap Jenis Makna dalam Ilmu Semantik - Puspa Ningrum, Aisyah Tinus; Dalimunthe, Anisah Azzahra; Yuhdi, Achmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The use of many figurative words makes it difficult for readers to understand the meaning contained in the beautiful stanzas of poetry. The purpose of the research is to analyze semantically with the object of study of a poem entitled